Examining the Impacts of Servant Leadership, Training, and Work Discipline on Employee Performance Improvement - Fachrial, Peppy (Dinasti International Journal of Management Science, 2024)
This study examines the impacts of servant leadership, training, and work discipline on employee performance improvement. The researchers embraced a comprehensive approach to comprehend the intricate interactions among these factors. The research methodology comprised a literature review, quantitative design, and statistical data analysis. The results reveal that servant leadership, training, and work discipline significantly contribute to improving employee performance in cargo companies, offering valuable insights for practitioners and researchers. The integration of servant leadership principles into organizational culture and the development of more effective employee development strategies are among the practical implications. The findings of this study also enhance the academic literature on the determinants of employee performance. The conceptual framework of the study is employed in this investigation, as it is the first to investigate the impact of each variable on employee performance in cargo companies: servant leadership, training, and discipline.